2015
DOI: 10.1002/ange.201411954
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (−)‐Caprazamycin A

Abstract: Caprazamycin A has significant antibacterial activity against Mycobacterium tuberculosis (TB). The first total synthesis is herein reported and features a) the scalable preparation of the syn‐β‐hydroxy amino acid with a thiourea‐catalyzed diastereoselective aldol reaction, b) construction of a diazepanone with an unstable fatty‐acid side chain, and c) global deprotection with hydrogenation. This report provides a route for the synthesis of related liponucleoside antibiotics with fatty‐acid side chains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…To date, several derivatives of uridylpeptide natural products have been generated through engineering of the organisms that produce the natural products or through semi-synthetic approaches and, as such, feature limited structural variation 17 18 19 20 21 22 23 24 25 . A number of synthetic studies have also been reported on uridylpeptide natural products and analogues 26 27 28 29 30 31 32 33 , some of which have been shown to possess antimicrobial activity 7 8 . The focus of the present study was to develop a rapid and divergent synthetic strategy to access a diverse library of sansanmycin analogues that would enable the determination of key structure-activity relationships specifically against Mtb.…”
Section: Resultsmentioning
confidence: 99%
“…To date, several derivatives of uridylpeptide natural products have been generated through engineering of the organisms that produce the natural products or through semi-synthetic approaches and, as such, feature limited structural variation 17 18 19 20 21 22 23 24 25 . A number of synthetic studies have also been reported on uridylpeptide natural products and analogues 26 27 28 29 30 31 32 33 , some of which have been shown to possess antimicrobial activity 7 8 . The focus of the present study was to develop a rapid and divergent synthetic strategy to access a diverse library of sansanmycin analogues that would enable the determination of key structure-activity relationships specifically against Mtb.…”
Section: Resultsmentioning
confidence: 99%
“…[27][28][29] However, until recently, the final complex compound of a caprazamycin family member, caprazamycin A (19, Scheme 1), including the unstable long chain acyl tail modification, had proven synthetically inaccessible. The first total synthesis of (−)caprazamycin A was performed by Takemoto and co-workers in 2015, 30 and the synthesis was further developed in 2019. 31 2.1.1 A recent total chemical synthesis of a complex uridine natural product -Challenges from previous efforts towards caprazamycin natural products (19) involved construction of the syn-b-hydroxyamino acid moiety, formation of the 1,4-diazepanone core, and the introduction of the fatty acid side chain (Scheme 1).…”
Section: Caprazamycinmentioning
confidence: 99%
“…The total synthesis of caprazamycin A has been reported and was accomplished in 23 steps. It will guide the synthesis of related uridyl liponucleoside antibiotics such as liposidomycin and A-90289 [77,78]. Although an analog of caprazamycin, CPZEN-45, has been anticipated as a new antituberculosis drug, the co-crystal structures of caprazamycin analogs to MraY and WecA will also provide information about other new potential drugs (Fig.…”
Section: Organic Synthesis and Biosynthesis Of Liponucleoside Antibiomentioning
confidence: 99%